Distribution Of Eel Fish (Anguilla bicolor) In Cibeureum River, Cilacap District - Sutirno Sutirno; Purnama Sukardi; Agatha Sih Piranti (Fakultas Biologi | Universitas Jenderal Soedirman, 2021)
Fish resources in the waters are very dependent on fish larvae resources. Catching eel from the size of the seed (glass eel) to the size of the adult eel has decreased in nature indicating that in the management of eel the economic aspect is more dominant than its conservation aspects. The purpose of this study was to design the management pattern of eel fish in Cibeureum River, Sidareja District, Cilacap Regency based on their ecology, water quality, and rate of exploitation. The research method used is explanatory research and sampling techniques using purposive sampling method in five sampling stations from upstream to downstream of the Cibeureum River. The research data were analyzed using descriptive analysis. The results of the study of the water quality of the Cibeureum River meet the water quality requirements as eel living areas in accordance with GR No.82 of 2001. The abundance of eel species has an Abundance Index (KR) 72.73 - 93.75%, Yellow Eel types have KR = 6,25 - 27.27%, Glass Eel and Silver Eel have abundance, KR = 0%. The distribution pattern of eel fish species of Elver and Yellow Eel has a random distribution pattern (Id = 0.95 and Id = 0.99). Glass Eel and Silver Eel do not have a distribution pattern (Id = 0). Growth rate of eel fish = 120.23 (1-. Total mortality rate (Z) of 2.88 per year that eel fish mortality in the Cibeureum River, mostly caused by fishing activities with exploitation rate (E) of 0.84 per year and it is thought to have exceeded the optimum value (overfishing) The management pattern of eel fish (Anguila bicolor) by limiting the time and area of capture as well as the important role of TPI, cooperatives and Pokmaswas (Community Watch Group) in the eel catchment area.